USM – CMU TO ESTABLISH COLLABORATIONS WITH EXCHANGE PROGRAMMES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 19 July 2016 Universiti Sains Malaysia (USM) hopes to establish collaborations with Chiang Mai University (CMU) Thailand, following the visit by representatives from CMU to USM today.